2012
DOI: 10.11113/jt.v59.2580
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dry and Wet Ball Milling Process on Critical Powder Loading and Mixture Properties of Fine WC-10Co-0.8VC Powder

Abstract: Micro powder injection molding (μPIM) has great potential for the production of micro cemented carbide parts that require high hardness and toughness. The main stages of the μPIM process include mixing the powder and organic binder, injecting, debinding, and sintering. High critical solid loading of submicron tungsten carbide (WC) powder is one of the requirements in the micro powder injection molding process, which is not obtained easily. This paper investigates the effects of ball milling on critical solid l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…This is confirmed by the SEM images shown in Figure 5 . The largest share of the smallest filler particles was recorded for W-KI, which may result from a change in the process conditions (i.e., the wet process’s implementation [ 54 ]), which results from the low KI melting point. Considering the increased fraction of the smallest particles, in the range below 0.1 µm, it can be assumed that the addition of the filler caused organofunctionalization of the expanded vermiculite and an additional intercalation of its structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is confirmed by the SEM images shown in Figure 5 . The largest share of the smallest filler particles was recorded for W-KI, which may result from a change in the process conditions (i.e., the wet process’s implementation [ 54 ]), which results from the low KI melting point. Considering the increased fraction of the smallest particles, in the range below 0.1 µm, it can be assumed that the addition of the filler caused organofunctionalization of the expanded vermiculite and an additional intercalation of its structure.…”
Section: Resultsmentioning
confidence: 99%
“…This is confirmed by the SEM images shown in Figure 5. The largest share of the smallest filler particles was recorded for W-KI, which may result from a change in the process conditions (i.e., the wet process's implementation [54]), which results from the low KI melting point.…”
Section: Characterization Of the Fillermentioning
confidence: 99%
“…Samples have been dried in an oven at 100 °C for 12 h. Zinc stearate was chosen as a dry milling medium. Zhang et al [39] have shown that the dry milling conditions allow the obtention of smaller grains in agglomerated particles while wet milling provides better dispersion of the particles [42].…”
Section: Methodsmentioning
confidence: 99%
“…Ball milling is widely used in tungsten carbide preparation to ensure a good homogenization of the different powders as well as to induce "mechanical alloying" [37,38]. The influence of ball milling parameters (medium, balls diameter, time) has been studied in different papers [39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, with a great technique and cost advantages, powder injection molding (PIM) is the most suitable method to produce complex shapes of cemented carbide components [2]. Basically, PIM was adjusted from metal injection molding process (MIM) [3]. MIM process consists of four main steps: mixing, injection molding, debinding, and sintering.…”
Section: Introductionmentioning
confidence: 99%